화장품 패키지디자인의 캐릭터 컬래버레이션이 구매에 미치는 영향 - 양은미; Yang Eun Mi; 임경호; Lim Kyung Ho (기초조형학연구, 2018)
제품을 구매할 때 패키지디자인은 제품의 기능만큼이나 중요한 역할을 한다. 화장품 패키지디자인은 화장품을 보호하고 제품의 기능을 소비자에게 잘 전달해 줌과 동시에 구매 욕구를 불러일으키는 역할을 한다. 시각적인 부각을 위한 트렌드 중 화장품 패키지디자인에서 캐릭터 컬래버레이션을 활용한 상품들이 늘어나고 있다. 그러나, 캐릭터 컬래버레이션 화장품에 대해 10대와 20대 여성층을 비교한 연구는 미비한 실정이다. 본 연구는 캐릭터 컬래버레이션의 개념에 대해 정의하고 그 사례에 대해 알아보았으며, 캐릭터 컬래버레이션이 구매에 어떠한 영향을 미치는지에 대하여 연구하였다. 연구 설계는 다음과 같다. 캐릭터 컬래버레이션에 대한 소비자들의 선호도와 구매 태도에 관한 문헌 연구 및 사례 연구를 바탕으로 캐릭터 컬래버레이션 화장품에 대한 인지도 및 선호도와 구매 의사를 조사하기 위한 문항을 구성하였다. 설문 대상은 만 12세에서 만 29세 여성 140명이며 화장품 브랜드는 2011~2017년 7년간 국내 매출 상위 1~7위 로드숍 중 캐릭터 컬래버레이션상품이 있는 화장품으로 한정하여 설문조사를 통해 인지도, 선호도 및 구매 행동을 분석하였다. 수집된 자료는 SPSS Statistics 23을 사용하여 분석하였으며 주된 통계 방법은 빈도 분석, 분산 분석이다. 캐릭터 컬래버레이션 화장품 패키지디자인에 대한 소비자 태도 분석 결과는 SNS 캐릭터의 영향으로 전체 모집군 50% 이상이 해외 유명 캐릭터들보다 국내 캐릭터에 높은 인지도와 선호도를 보였으며, 전자제품에서의 캐릭터 컬래버레이션 인지도는 비교적 낮았다. 중학생은 캐릭터컬래버레이션의 적용이 중요한 요소였으나, 성인은 SNS의 영향으로 생겨난 개인의 경험에서 생겨난 기호가 중요요인이 된다고 분석된다. 연령별로 선호도와 구매 의사의 영향에서 차이를 나타냄을 알 수 있다. 본 연구 결과는 향후 캐릭터 컬래버레이션 화장품 패키지디자인의 브랜드 및 전략 수립의 근거자료가 될 수 있을 것이다. Package design plays an important role as much as the function of product when consumers make decisions. Cosmetics package design not only protects cosmetic and introduces its function to consumers, but also stimulates their desire. The trends for emerging of visualization which increased products utilizing character collaboration. But, we face lack of studies which compare with teenage girls and those in their 20s regarding these products. This study defines the concept of character collaboration and identifies examples. Furthermore, this study indicates how character collaboration affects consumer's decision to buy. Research design is going into follows this direction for several reasons. The researcher consisted of several questions to identify the degree of preference that of recognition, and the willingness to purchase for character-collaborated cosmetics based on similar academic references and examples. Therefore, survey subjects are 140 females from age 12 to age 29. Cosmetic brands are limited to those with character collaboration among the Top 1-7 brands on domestic sales from 2011 to 2017. This research analyzes the degree of recognition, preference and purchase behavior through survey methods. Collected figures are analyzed by SPSS Statistics 23 and the major statistic method is frequency analysis and variance analysis. As a result of consumer attitude analysis, more than 50% of the whole population shows higher recognition and preference on Korean characters than popular foreign characters, thanks to the effect of SNS. It also tells the way of application is an important factor for middle school students, however, for adults, preference made from personal experience via SNS is most important. The results of the two factors differ based on the age of consumers. This research will be the cornerstone to contribute to future branding and strategy of cosmetics package design with character collaboration.